Flourishing Organisational Citizenship Behaviour through Job Characteristics - Shahi, Bhupendra Jung; Dahal, Rewan Kumar; Sharma, Bhanu Bhakta (Journal of Business and Social Sciences Research, 2022)
Researchers' contributions in identifying predictors of organisational citizenship behaviours are appreciable, and still, contextual study of job characteristics as an antecedent of enhancing employees' citizenship behaviours will be valuable for the banking and insurance sectors. This study is an endeavour to investigate the way of association and influence of perceived job characteristics on organisational citizenship behaviours (OCBs). Cross-sectional survey data were obtained from 221 employees involved in varying natures of jobs in the Nepalese Banking and Insurance industry. Correlation analysis revealed the positive association of perceived job characteristics with organisational citizenship behaviours. Similarly, the regression analysis suggested that perceived overall job characteristics positively and significantly predicted organisational citizenship behaviours (OCB-I, OCB-O, and overall OCB). The study is expected to add value to job design considerations for flourishing citizenship behaviours from the context of the Nepalese banking and insurance sectors.